Source material from crosses among Solanum L. spp. for potato breeding - N. M. Zoteyeva; Z. Z. Evdokimova (Труды по прикладной ботанике, генетике и селекции, 2022)
Background. Late blight (agent: Phytophthora infestans (Mont.) de Bary) is one of the most destructive diseases for potato. The climate conditions in the northwest of Russia are very favorable for annual late blight infestation. Spreading of the pathogen leads to significant harvest losses. A promising breeding strategy is to expand the genetic diversity of resistance sources.Materials and methods. Resistance of experimental hybrid clones to late blight, their ability to form tubers under long daylight conditions, and a number of agronomic traits were studied using standard methods.Results. Long-term evaluation data were obtained for original interspecies potato hybrids concerning their resistance to late blight. The hybrids were also assessed for their yield and agronomic tuber characteristics. Some of the produced interspecies hybrids demonstrated field resistance to late blight, high tuber yield, and good agronomic traits. Clones derived from some cross combinations significantly exceeded both parents in tuber yield per plant and tuber size.Conclusions. Crosses between potato cultivars and various late blight resistance sources made it possible to combine in hybrid clones the genes of wild and cultivated Andean species and Solanum tuberosum L. with different pedigrees. Productive hybrid clones with resistance to late blight and good agronomic characteristics promise to become useful material for potato breeding programs.